2018
DOI: 10.1039/c7nj03212a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nature of the nucleophile and solvent on an SNAr reaction

Abstract: The reaction of 2,4-dinitrobenzenesulfonyl chloride toward propylamine was kinetically evaluated in 19 organic solvents and 10 ionic liquids as reaction media. This study was compared with a previous study to experimentally show that solvent effects and the nature of the reacting pair drastically affect the reaction rate and the reaction mechanism. While the reaction of the reference electrophile 2,4-dinitrobenzenesulfonyl chloride with piperidine is favored in polar solvents with the ability to donate or acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Therefore, the higher polarity solvent may be a better insulator of the charges of the thiolate nucleophile, and the Meisenheimer complex formed in the reaction. [ 33 ] The outlier to this trend is propylene carbonate which has the highest polarisability and dielectric properties of the solvents investigated, yet seems to be less efficient than DMSO in promoting substitution. This may be due to its higher viscosity affecting efficient mixing or perhaps another property not considered here.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the higher polarity solvent may be a better insulator of the charges of the thiolate nucleophile, and the Meisenheimer complex formed in the reaction. [ 33 ] The outlier to this trend is propylene carbonate which has the highest polarisability and dielectric properties of the solvents investigated, yet seems to be less efficient than DMSO in promoting substitution. This may be due to its higher viscosity affecting efficient mixing or perhaps another property not considered here.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a complete study based on the reaction of DNBSCl with piperidine was performed in 17 RTILs considering water as a solvent reference. This study identified three groups of RTILs showing 1-ethyl-3-methylimidazolium dicyanamide (EMIMDCN) as the best solvent considering all the studied RTILs and 21 COS [12,40]. EMIMDCN shows a catalytic behavior attributed to its high polarizability given by the dicyanamide anion (DCN − ), which presents a highly rich π electron density, and its size could be in relationship with steric hindrance effects.…”
Section: S N Ar Reactions In Ionic Liquidsmentioning
confidence: 99%
“…The concept of polarity has been defined as the sum of all possible intermolecular interactions between the solvent and the solute, including specific interactions, for instance, HB effects, dipole-dipole, dipole-induced dipole, electron pair acceptor-electron pair donor, and acid-base interactions [1,33]. Gazitúa et al [12,40] studied the solvation patterns of 21 COS and water over the reaction between 2,4-dinitrophenylsulfonyl chloride (DNBSCl) with SA amines in order to determine the solvent polarity effect on the reaction mechanism. Note that solvent polarity became relevant only in the reactions that proceeded by the non-catalyzed route.…”
Section: Polarity and Solvent Effectsmentioning
confidence: 99%
“…Still, when tested under strictly dry alkaline conditions, in which hydroxide microsolvation is limited, these ammonium salts decomposed very rapidly by the expected mechanisms . This is another example in which the solvation environment, and particularly water molecules, can affect reaction mechanisms heterogeneously . Therefore, new paradigms of QAs which may decompose through different reaction mechanisms is of supreme importance, as it opens new avenues for the development of more stable cations.…”
Section: Introductionmentioning
confidence: 99%